The ASC-1 Complex Disassembles Collided Ribosomes - Juszkiewicz, Szymon (Mol Cell, 2020)
Translating ribosomes that slow excessively incur collisions with trailing ribosomes. Persistent collisions are detected by ZNF598, a ubiquitin ligase that ubiquitinates sites on the ribosomal 40S subunit to initiate pathways of mRNA and protein quality control. The collided ribosome complex must be disassembled to initiate downstream quality control, but the mechanistic basis of disassembly is unclear. Here, we reconstitute the disassembly of a collided polysome in a mammalian cell-free system. The widely conserved ASC-1 complex (ASCC) containing the ASCC3 helicase disassembles the leading ribosome in an ATP-dependent reaction. Disassembly, but not ribosome association, requires 40S ubiquitination by ZNF598, but not GTP-dependent factors, including the Pelo-Hbs1L ribosome rescue complex. Trailing ribosomes can elongate once the roadblock has been removed and only become targets if they subsequently stall and incur collisions. These findings define the specific role of ASCC during ribosome-associated quality control and identify the molecular target of its activity.